Performance of honey bee (Apis mellifera) on toria (Brassics rapa var napus) under mid-hill subhumid zone of Himachal Pradesh - SRIVASTAVA, S; CHANDEL, Y S; KUMAR, ARUN; KASHYAP, N P; KUMAR, ASHWANI (The Indian Journal of Agricultural Sciences, 2013)
Performance of honey bee (Apis mellifera L.) was studied on toria [Brassica rapa (L.) Thell. emend. Matzger var napus L.; syn B. campestris L. ssp oleifera (Metzger) Sinsk. var toria ] in mid - hill subhumid zone of Himachal Pradesh. This bee species was unable to store surplus honey. Instead, colonies at the end of flowering were found to decrease in strength (37.6%) and brood realing slowed down (71.5%) when compared with flower-initiation stage of the crop. Low temperature during flowering period of the crop leading to supressed activity and less nectar load/bee were found the causes of poor performance by this bee species.